Heat and mass transfer - Karwa, Rajendra (Springer, 2016)
This textbook presents the classical treatment of the problems of heat transfer in an exhaustive manner with due emphasis on understanding of the physics of the problems. Another special feature of the book is a chapter on introduction to design of heat exchangers and their illustrative design problems.
Keywords: Heat -- Transmission.; Mass transfer.; elektronické knihy; electronic books